Comparison of IL-10 gene promoter polymorphisms and haplotypes between high-grade squamous intraepithelial lesions or cervical cancer and negative cervical cytology - Amaxsell Thiago Barros de Souza; Deborah Luisa de Sousa Santos; Fernanda Silva Medeiros; Kleyton Thiago Costa de Carvalho; George Alexandre Lira; Ricardo Ney Cobucci; Kassio Michell Gomes de Lima; Norma Lucena-Silva; Eduardo Antônio Donadi; Janaina Cristiana de Oliveira Crispim (Scientific Reports)
Abstract Cervical cancer, a leading cancer among women, is strongly associated with Human Papillomavirus infection, but host genetic factors also contribute to the progression from high-grade squamous intraepithelial lesions (HSIL) to invasive cancer. Interleukin-10 (IL-10), an immunosuppressive cytokine, may influence susceptibility to HSIL and cervical cancer through genetic variations. This study aimed to compare IL-10 gene promoter polymorphisms, -1082 A > G and − 819T > C, in women diagnosed with HSIL or cervical cancer and those with negative for intraepithelial lesion or malignancy (NILM). In this case-control study, 309 women were analyzed, including 142 with HSIL or cervical cancer and 167 controls with NILM. Blood samples were collected for DNA extraction and genotyping of polymorphisms through PCR amplification. Statistical analyses included comparisons of genotype and allele frequencies, haplotype frequency, and assessments of Hardy-Weinberg equilibrium and linkage disequilibrium. The mean age was 33.4 years for cases and 41.7 years for controls (p < 0.05). For the − 1082 A > G polymorphism, the GG genotype was significantly associated with a decreased risk of HSIL and cervical cancer (p = 0.0266, OR = 0.35). Recessive model (GG vs. AA + AG) confirmed this association (p = 0.0045, OR = 0.29). AC/GC diplotype was associated with a 2-fold increased risk of cervical lesions. Further studies are needed to confirm our results.